Morphology Tuning and Its Role in Optimization of Perovskite Films Fabricated from A Novel Nonhalide Lead Source. Issue 23 (1st November 2020) - Gu, Jinwen; Li, Faming; Wang, Zenghui; Xie, Yiran; Yan, Lihe; Zeng, Peng; Yu, Hua; Liu, Mingzhen
Abstract: Usage of nonhalide lead sources for fabricating perovskite solar cells (PSCs) has recently attracted increasing attention as a promising route toward realizing high quality PSC devices. However, the unique role of nonhalide lead sources in improving perovskite film morphology and PSC performance has largely remained unexplored, impeding broader application of these materials. Here, it is demonstrated that by using a new nonhalide lead source, lead formate (Pb(HCOO)2 ), good control of perovskite film morphology can be achieved. With the usage of lead formate, PbI2 can nicely border the perovskite grain boundaries (GBs) and form domain "walls" that segregate the individual perovskite crystal domains. The PbI2 at the GBs lead to significant improvement in film quality and device performance through passivating the defects at the perovskite GBs and suppressing lateral carrier diffusion. An impressive carrier lifetime at the microsecond scale ( τ 2 = 1714 ns) is achieved, further with an optimal power conversion efficiency of 20.3% for the resulting devices. This work demonstrates a promising and effective method toward fabricating high‐quality perovskites and high‐efficiency PSCs. Abstract : A new nonhalide lead source, lead formate (Pb(HCOO)2 ), is used to prepare perovskite solar cells. Using Pb(HCOO)2 forms PbI2 domain "walls" bordering perovskite grains, leading to an ultralong carrier lifetime (≈1.7 microseconds) and a record‐high power conversion efficiency (>20%) for MAPbI3 based devices produced from nonhalide lead sources.